Cognitive Domains in an English Teacher's Classroom Discourse at Petra Language Center - Herlin Kristina; Henny Putri Saking Wijaya (Kata Kita: Journal of Language, Literature, and Teaching, 2024)
Asking questions in class can facilitate a smooth flow of discussion and encourage students’ active participation. Teachers help students to have a better understanding by giving questions related to the students’ cognitive domains. Therefore, this study aims to find the cognitive domains employed by an English teacher to primary students in the Children 3B English class atPetra Language Center. The theoretical framework is Anderson and Krathwohl's (2001) cognitive domains. Employing a qualitative approach, the writers transcribed and analyzed the teacher's WH questions in both English and Indonesian languages during three meetings before the final exams. The analysis showed that the teacher utilized two of six cognitive domains: remember and understand. The teacher primarily employed remember cognitive domain. In conclusion, significant factors influencing the outcomes include the learning objectives and the students' proficiency levels. Future research should expand to the Teenager class at Petra Language Center to examine the teacher's response to students' answers to the teacher’s questions.